발아현미 선식의 품질 및 이화학적 특성 - 방애솔(Yae-Sol Bang); 장은희(Eun Hee Jang); 정현정(Hyun-Jung Chung) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2017)
The quality and physicochemical characteristics of newly developed Sunsik products were investigated. Sunsik A, B, and C were prepared under different roasting temperatures and times (A: 220°C, 15 min; B: 220°C, 25 min; C, D, E: 230°C, 15 min). Sunsik D was prepared using grain flours passed through a 100 mesh screen, whereas the other products were passed through a 140 mesh screen. Sunsik E was prepared by the addition of germinated grains. The moisture content of Sunsik products ranged from 3.24-7.10%. The viscosity and sugar content ranged from 57-74 cP and 1.5-1.7°Bx, respectively. The pH values were similar among the samples. Sunsik D had the highest gelatinization enthalpy, whereas Sunsik C had the lowest. The viable cell counts were in the range from 3-4 log CFU/g and coliform groups were not detected. Sunsik B and E had higher scores for savory flavor and sweet taste than other Sunsik products.